Efficacy and safety of inhaled corticosteroids relative to fluticasone propionate: a systematic review of randomized controlled trials in asthma. (3rd October 2017) - Yeo, See-Hwee; Aggarwal, Bhumika; Shantakumar, Sumitra; Mulgirigama, Aruni; Daley-Yates, Peter
ABSTRACT: Introduction : Many trials have been published comparing inhaled corticosteroid (ICS) treatments in asthma. However, mixed results necessitate the summarization of available evidence to aid in decision-making. Areas covered : This systematic review evaluated randomized controlled trials (RCTs) that compared the efficacy and safety of inhaled fluticasone propionate (FP) with other ICS including beclomethasone dipropionate (BDP), budesonide (BUD) and ciclesonide (CIC). PubMed was searched and 54 RCTs that fit pre-determined criteria were included. Endpoints evaluated included lung function, asthma symptom control, exacerbation frequency, reliever use, quality of life and steroid-related side effects. Expert commentary : Across all studies, FP was associated with either more favorable or at least similar efficacy and safety, in comparison with BDP or BUD. This observation may be related to FP's higher relative potency and almost negligible oral bioavailability. FP was comparable to CIC for efficacy. However, CIC appeared to have a smaller impact on cortisol levels than FP, which is likely due to CIC's incomplete conversion to active metabolite (des-CIC) and the lower potency of des-CIC compared with FP. Although there were no significant differences in evaluated outcomes after treatment with different ICS in the majority of studies, some observed differences could be explained by their respective pharmacodynamic and pharmacokinetic properties.